Identification and pathogenicity of Fusarium spp. in row crops in Nebraska. (June 2018) - Parikh, L.; Kodati, S.; Eskelson, M.J.; Adesemoye, A.O.
Abstract: Fusarium spp. comprise multiple pathogenic fungi that cause root rot in row crops, including corn, soybean, and wheat, and have wide geographic and host ranges. Studies to identify which Fusarium spp. are the prevalent disease-causing pathogens in a given region are important for developing disease management strategies. This study aimed i) to isolate, identify, and determine the intraspecific diversity of Fusarium spp. associated with root rot in corn, soybean, and wheat crops in Nebraska and ii) to determine the cross-pathogenicity of recovered isolates among these crops. In 2015 and 2016, 137 isolates were obtained from 20 counties in Nebraska and 62 of which represented all morphological groups were selected and identified by sequencing of the internal transcribed spacer regions of rDNA and the beta tubulin. The pathogenicity of 28 isolates in corn, soybean, and wheat crops was evaluated. Among the 11 phylogenetically distinct species identified, F. oxysporum was the most abundant, followed by F. graminearum and F. acuminatum, and these species are found in all geographic regions of Nebraska. However, F. graminearum was considered to be the most virulent species because five of the eight most virulent strains that demonstrated cross-pathogenicity among the three crops were F. graminearum strains. Other identified species were F. solani, F. equiseti, F. redolens, F. fujikuroi, F. avenaceum, F. culmorum, F. verticillioides, and F. sporotrichioides . Highlights: Ten species of Fusarium are associated with root rot in row crops in Nebraska. F. oxysporum, F. graminearum, F. accuminatum, F. equiseti, F. avenaceum, F. proliferatum, and F. solani cause Fusarium root rot in corn, soybean, and wheat crops. F. oxysporum is the most abundant species while F. graminearum presents the highest risk of causing root rot in Nebraska. Cross-pathogenicity of Fusarium spp. among corn, soybean, and wheat crops is high.